Energy Efficiency of a Greenhouse for the Conservation of Forestry Biodiversity. (13th February 2013) - Marucci, Alvaro; Carlini, Maurizio; Castellucci, Sonia; Cappuccini, Andrea
Abstract : Forest biodiversity conservation is one of the most interesting and crucial problems in forestry world. Currently, the conservation methods are based on two phases: the conservation of seeds at low temperatures and the multiplication of vegetable material. This latter operation can be successfully developed in properly designed greenhouses. The aim of this paper is to define a type of greenhouse which is particularly suitable for plant material propagation in order to preserve forest biodiversity in the area of the Central Italy. Some general parameters were first defined for a correct planning of the structure, such as: the shape of the section, volume, cover material, systems for heating and cooling, and those for the control of the internal microclimate parameters (light, air temperature, and relative humidity). Considering the construction characteristics and the climatic conditions of the place, the internal microclimatic conditions have been later determined by the useful implementation in TRNSYS in order to analyse the energy efficiency of the greenhouse.